HRQoL Evaluation of Pediatric Osteogenesis Imperfecta with Zoledronic Acid Therapy - Martanto, Tri Wahyu; Rahman, Hamzah Rafly; Kurniawati, Patricia Maria (Universitas Airlangga, 2023)
Background: Zoledronic acid, a bisphosphonate, increases bone mineral density (BMD), which can reduce clinical manifestations in osteogenesis imperfecta. This study investigates the impact of zoledronic acid therapy on the quality of life of pediatric patients with osteogenesis imperfecta.Methods: A retrospective analytical study was conducted on 16 pediatric patients with osteogenesis imperfecta who received intravenous zoledronic acid. Quality of life was assessed before and after therapy using the PedsQL 4.0 questionnaire. A paired t-test was used to analyze changes in each domain of the PedsQL 4.0. The results were expressed as an adjusted odds ratio with a 95% confidence interval. A p <0.05 was considered statistically significant.Results: A significant increase was found in the children’s self-reported social performance (+12.083, p = 0.023) and proxy-reported physical performance, social performance, and total score (+14.844, p = 0.006; +10.625, p = 0.010; +10.364, p = 0.006, respectively). An insignificant increase was found in child-reported physical performance, school performance, and total score (+8.833, p = 0.148; +5.000, p = 0.359; +7.065, p = 0.115, respectively), and proxy-reported emotional and school performance (+2.500, p = 0.669; +6.250, p = 0.167, respectively). An insignificant decrease was found in child-reported emotional performance (-2.500, p = 0.669).Conclusion: After receiving bisphosphonate therapy, pediatric patients with osteogenesis imperfecta experienced an increased quality of life. Physical and social aspects showed the greatest improvement. Emotional well-being showed the lowest increase in the child's perception, with a decrease in parent perception after therapy.